Antimicrobial susceptibility of Neisseria gonorrhoeae in Barcelona during a five-year period, 2013 to 2017 - Salmerón, Paula (Euro Surveill, 2020)
INTRODUCTION: Increasing rates of antimicrobial resistance in Neisseria gonorrhoeae cause problems for treating gonorrhoea. AIM: This observational study aimed to describe isolates from all patients found infected with N. gonorrhoeae, in Barcelona, Spain, between 2013 and 2017, and with available antimicrobial susceptibility data. METHODS: Minimum inhibitory concentrations (MICs) of penicillin (PEN), cefixime (CFM), ceftriaxone (CRO), azithromycin (AZM), ciprofloxacin (CIP), spectinomycin (SPT), fosfomycin (FOF) and gentamicin (GEN) were determined by E-test. Susceptibility was assessed using clinical breakpoints from the European Committee on Antimicrobial Susceptibility Testing. Time trends for PEN, CFM, AZM and CIP were investigated using logistic regression. RESULTS: Of 1,979 patients with infection (2,036 isolates), 1,888 (95.4%) were men. Patient median age was 32 years. The proportions of isolates resistant to extended-spectrum cephalosporins were low, with 0.3% (5/1,982) resistant to CRO and 4.9% (98/1,985) to CFM. AZM resistance prevalence was 2.7% (52/1,981), including 16 isolates detected in 2016 and 2017, with high-level resistance. For CIP, 51.3% (1,018/1,986) of isolates were resistant, and for PEN, 20.1% (399/1,985). All isolates were susceptible to SPT. MIC(50) and MIC(90) values of GEN were 4 and 6 mg/L and of FOF 12 and 24 mg/L, respectively. Between 2013 and 2017, PEN and CFM resistance rates each decreased from 28.1% (92/327) to 12.2% (70/572) and from 8.3% (27/327) to 4.4% (25/572) (p ≤ 0.0073). In contrast, AZM resistance prevalence appeared to increase from 1.5% in 2014 (5/340) to 3.0% (17/572) in 2017. No trend was identified for CIP. CONCLUSION: Antimicrobial susceptibility surveillance is important to timely detect new phenotypes and trends.